User Interface and User Experience Design of Coffee Bean Sales Application with Design Thinking: Perancangan User Interface dan User Experience Aplikasi Penjualan Biji Kopi dengan Design Thinking - Widayanti Kusumaningrum; Erwin Widodo; Endroyono (Academia Open, 2025)
General Background: Coffee is a vital commodity in Indonesia, yet local coffee bean sales remain limited despite substantial production. Specific Background: The challenges in the coffee industry include fluctuating prices, complex distribution channels, and limited access to broader markets for small-scale farmers. Knowledge Gap: Previous studies on coffee sales applications have primarily focused on usability testing, lacking comprehensive solutions for stock management, branding, and distribution efficiency. Aims: This study aims to design and develop a user-friendly application for coffee bean sales, MOWK’S COFFEE, using the Design Thinking methodology to enhance User Interface (UI) and User Experience (UX). Results: Through iterative processes of empathizing, defining, ideating, prototyping, and testing, the research produced a validated application prototype that significantly improved transaction ease, stock management, and distribution processes while enhancing user satisfaction. Novelty: Unlike prior research, this study integrates iterative user feedback into every design stage, addressing not only interface usability but also operational complexities in coffee supply chains. Implications: The findings demonstrate that applying Design Thinking to e-commerce applications can strengthen the sustainability of local coffee production by connecting farmers directly with consumers, reducing reliance on intermediaries, and potentially boosting income for coffee stakeholders.Highlight : Designing the UI and UX of a coffee bean sales application. Using the Design Thinking method to understand user needs. Improving local coffee distribution and user experience. Keywords : Perkembangan Biji Kopi Indonesia, Design Thinking, User Interface, User Experience, E-commerce